2016
DOI: 10.2147/ccid.s115256
|View full text |Cite
|
Sign up to set email alerts
|

Safety and performance of cohesive polydensified matrix hyaluronic acid fillers with lidocaine in the clinical setting – an open-label, multicenter study

Abstract: Cohesive polydensified matrix (CPM®) hyaluronic acid fillers are now available with or without lidocaine. The aim of this study was to investigate the safety and performance of CPM® fillers with lidocaine in the clinical setting. In an open-label, prospective, postmarketing study, 108 patients from seven sites in Germany and Denmark were treated with one or more lidocaine-containing CPM® fillers. Performance was assessed using the Merz Aesthetics Scales® (MAS). Pain was rated on an 11-point visual analog scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“… 28 Similar findings were revealed in overseas and Asian studies comparing HA fillers with and without lidocaine for NLF correction. 26 28 , 30 32 It has also been shown that the use of topical anesthesia does not affect the difference in pain scores between HA fillers with and without lidocaine, 33 which was corroborated in the current study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“… 28 Similar findings were revealed in overseas and Asian studies comparing HA fillers with and without lidocaine for NLF correction. 26 28 , 30 32 It has also been shown that the use of topical anesthesia does not affect the difference in pain scores between HA fillers with and without lidocaine, 33 which was corroborated in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…Published studies comparing HA fillers with and without lidocaine for NLF correction suggest comparable effectiveness for reducing the severity of wrinkles. [26][27][28][30][31][32] It has been reported that lidocaine can be easily dissolved in HA gel without altering its concentration and properties, thus enabling the filler to effectively reduce procedural pain while not compromising effectiveness. 30 In addition to WSRS improvements compared with baseline and favorable results regarding pain sensation for BEL versus the control, the current study's GAISand GICS-based response rate results indicate that both investigators and subjects perceived improvements throughout the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The positive results achieved in cheek augmentation are in line with previous studies. 17 , 18 The long-lasting treatment success in cheek augmentation may be attributed to the high capacity of CPM-HA-VL to resist vertical and dynamic compression which makes CPM-HA-VL ideal for achieving an excellent volumizing effect following deep implantation. 19 Clinical studies and postmarketing clinical observations have shown a lasting effect without touch-up up to 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that lidocaine integrated into the filler reduced the perception of pain during the injection and correlated with higher patient satisfaction. 26 Although injection site reactions such as redness, swelling, and bruising are expected with any type of dermal filler injection, 17 only 1 event of redness was reported. Consistently, most patients in the present study stated their willingness to repeat the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Outro estudo de seguimento clínico aberto, multicêntrico, prospectivo, pós-comercialização, realizado em sete locais na Alemanha e na Dinamarca, realizado com 108 pacientes, sendo 102 mulheres e 6 homens, com o objetivo de avaliar a segurança e o desempenho dos preenchedores de AH com lidocaína, confirmou a segurança e o desempenho do AH, promovendo melhorias estéticas relacionadas a rítides, perda de volume facial e/ou plenitude labial. Os próprios pacientes relataram alto nível de satisfação com os resultados estéticos e baixo nível de desconforto durante os procedimentos 31 .…”
Section: Classificação Da Região Indicações Referênciasunclassified